A multi‐port interconnected magneto‐electric dipole antenna array for 5G applications. Issue 5 (27th February 2023) - Chen, Zihao; Zhang, Wenxu; Wang, Kai‐xu
Abstract: This letter reports a 28‐GHz multi‐port magneto‐electric (ME) dipole array for 5G applications. The proposed antenna array enlarges the system polarization diversity with the capability of being utilized as a balanced antenna, a dual‐polarized antenna and a circularly polarized antenna. Co‐planar waveguide (CPW) lines are used to connect ME dipole radiators to achieve a high gain with a simple feeding structure. The proposed antenna array exhibits a −10 dB impedance bandwidth of 12.8% and a maximal peak realized gain of 13.52 dBi as a balanced antenna, and exhibits a −10 dB impedance bandwidth of 28.57%, a 3‐dB axial ratio (AR) bandwidth of 16% and a maximal peak realized gain of 12.15 dBi as a circularly polarized antenna. Abstract : This letter reports a 28‐GHz multi‐port magneto‐electric (ME) dipole array for 5G applications. The proposed antenna array enlarges the system polarization diversity with the capability of being utilized as a balanced antenna, a dual‐polarized antenna and a circularly polarized antenna. Co‐planar waveguide (CPW) lines are used to connect ME dipole radiators to achieve a high gain with a simple feeding structure.